Tax Arbitrage and Labor Supply - Jonas Agell; Mats Persson (Uppsala University, Department of Economics, 1997)
We examine how tax avoidance in the form of trade in well-functioning asset markets affects the basic labor supply model. We show that tax arbitrage has dramatic implications for positive, normative and econometric analysis of how taxes affect work incentives.
urn:nbn:se:uu:diva-2394
Keywords: H21; H23; H24; 330; Labor supply; progressive income taxation; tax arbitrage